Experimental analysis of lengthwise/transversal thermal characteristics and jet flow of large-format prismatic lithium-ion battery. (August 2021) - Zhou, Zhizuan; Zhou, Xiaodong; Wang, Dong; Li, Maoyu; Wang, Boxuan; Yang, Lizhong; Cao, Bei
Highlights: Thermal runaway characteristics of prismatic batteries with lengthwise and transversal placements are investigated. The jet flow behavior of the battery during thermal runaway is analyzed in detail. A method is proposed to estimate the jet velocity based on mass loss rate. Abstract: Lithium-ion batteries (LIBs) are among the most promising technologies for electric vehicles and electric energy storage systems, while the safety accidents associated with thermal runaway happen frequently. Thermal characteristics and the jet behavior of prismatic LIBs under overheating conditions are still unclear. In this study, the thermal runaway characteristics of LIBs under lengthwise and transversal placements, such as battery surface temperature, voltage and mass loss are investigated through the overheating experiments. Results show that the center and bottom of the LIB surface of lengthwise placement have higher temperatures during thermal runaway. Compared with lengthwise placement, transversal placement accelerates the occurrence of thermal runaway under overheating conditions. The onset temperature of the safety valve opening is 129 °C, which is not affected by electrical energy stored inside the battery and placements. To comprehensively understand the prismatic LIB jet flow, a method is proposed to determine the jet velocity at the safety valve based on mass loss using mathematical deductions. The jet behavior, internal pressure and gas generation rate are also quantitatively characterized by experiments. The maximum jet velocity occurs with a value of 42.05 m/s occurs at the moment when the safety valve opens. This work further reveals thermal abuse characteristics and jet behavior of prismatic LIBs, the research outcomes of which provide guidance for the safe design and thermal hazard prevention in battery storage systems.